A comparative study between conventional skin sutures, staples adhesive skin glue for surgical skin closure - B. B., Ananda; J., Vikram; B. S., Ramesh; Khan, Hosni Mubarak (International Surgery Journal, 2019)
Background: The signature of a surgeon is ‘scar’. Skin closure technique should be technically easy, acceptable, speedy and economical. Sutures and staples remain the mainstay of techniques. However, the use of GLUE is increasing in clinical practice. Authors compared all the three techniques in terms of time efficacy, post-operative pain, wound complications, cosmesis and cost-effectiveness. Methods: A 2-year prospective randomized controlled study was conducted on 90 healthy patients comparing tissue glue, staplers and sutures in primary wound closures following elective surgeries in the Department of General Surgery at BRAMC (October 2015 to October 2017). Results: The patients in the three groups were analyzed using chi-square, ANOVA, Fisher Exact test, and results were formulated. Staples consumed less time for application with a mean of 53.3 seconds when compared to glue (103.97 seconds) and sutures (294.97 seconds). Glue gave best results in terms of less post-operative pain. Mean VAS score calculated at 12,24,48,72 hrs was 63.13,42.10,16.94,7.27 and at 7 days was 4.73. The wound ASEPSIS score calculated on 3rd, 5th, and 7th day. Cosmesis score on 7th day, 1st month and 5th month was calculated using modified hollander and VAS cosmesis scale. Mean score with glue was 5.83,88.90 and 96.13 respectively. Cost of material including length of hospital stay for glue was also effective with 3.47 days on an average. All the above proved statistical significance. Conclusions: Staples application is faster, consumes less significant time than glue and sutures. Skin glue gives the best results in terms of less post-operative pain, wound asepsis, better cosmesis and cost-effectiveness. The concept of tissue glue is a safe, attractive, and effective alternate over other conventional methods of wound closures following elective surgeries.